2022
DOI: 10.1172/jci143762
|View full text |Cite
|
Sign up to set email alerts
|

The changing role of natural killer cells in cancer metastasis

Abstract: Conflict of interest: AJE has the following patents: WO2016183183A1, Autoimmune antibodies for use in inhibiting cancer cell growth; and US20140336282A1, Molecular signatures of invasive cancer subpopulations. AJE has the following pending patent applications: 63/087,063, Methods for identifying modulators of natural killer cell interactions; and 63/183,884, Methods of identifying anti-metastatic agents. ISC has the following pending patent applications: 63/087,063, Methods for identifying modulators of natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 151 publications
3
29
0
Order By: Relevance
“…Previously in ex vivo and mouse models, we observed that NK cells can be ’reprogrammed’ after exposure to malignant mammary epithelial cells to promote tumor outgrowth (10, 11). To determine the human significance of this finding, we first generated a signature of mouse reprogrammed NK (rNK) cells based on an experiment (10) comparing the transcriptomes of healthy NK cells to tumor-exposed NK cells that we found to be tumor promoting (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously in ex vivo and mouse models, we observed that NK cells can be ’reprogrammed’ after exposure to malignant mammary epithelial cells to promote tumor outgrowth (10, 11). To determine the human significance of this finding, we first generated a signature of mouse reprogrammed NK (rNK) cells based on an experiment (10) comparing the transcriptomes of healthy NK cells to tumor-exposed NK cells that we found to be tumor promoting (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Their cytotoxic activity is regulated by a series of functionally activating and inactivating receptors. After tumor exposure, the balance of activating and inactivating receptors can change, and they can lose their cytotoxic activity, proliferative capacities, or even become tumor-promoting (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…MDSC-CTL interactions are important given the primary function of intratumoral MDSCs is suppression of CTLs (1, 6, 15, 16). MDSC-NK interactions are also important (2022, 24, 25), and NK cells are increasingly being studied as an immune population specifically affected by tumor cells to promote metastasis (46, 47). A schematic diagram of the model is provided in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…NK cells have been found altered in their phenotype and functions in diverse solid and hematological cancers [136,137]. In solid cancers, hypofunctional NK cells have been found both at tumor tissue and peripheral levels [136][137][138][139].…”
Section: Nk Cellsmentioning
confidence: 99%
“…NK cells have been found altered in their phenotype and functions in diverse solid and hematological cancers [136,137]. In solid cancers, hypofunctional NK cells have been found both at tumor tissue and peripheral levels [136][137][138][139]. As shared features of cell anergy in cancers, NK cells have been reported have decreased levels of NKG2D (a major activator receptor), together with impaired degranulation capabilities and reduced production and release of cytolytic molecules, such as perforin, granzymes, and IFNγ (Figure 2I) [136,140].…”
Section: Nk Cellsmentioning
confidence: 99%